Structural changes in molten CdTe - Shcherbak, L.; Feychuk, P.; Plevachuk, Yu.; Dong, Ch.; Sklyarchuk, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Shear viscosity (h) measurements of CdTe and CdTe + 2 at% In melts were performed using a cup viscometer up to 1403 K. The h(T) dependencies obtained during slow heating and cooling (Vh/c = = 10-15 K/h) show hysteresys near a melting point. According to the η(T) dependencies data drastic changes the melts structure occurred at 1376 K both during the heating and cooling of the melts.